2010
DOI: 10.1021/cr900152h
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Statistical and Numerical Methods for Spectroscopic Characterization of Protein Structural Evolution

Abstract: Victor worked in the group of Prof. Tolstorozhev in Minsk (Belarus) and studied 8-azasteroid compounds using submicrosecond time-resolved fluorescence. In 2004, he was admitted to the State University of New York, where as part of his Ph.D. studies he conducted research in the field of quantitative deep UV resonance Raman spectroscopy under the supervision of Professor Lednev. His areas of interest are quantitative modeling of resonance Raman scattering, signal separation, chemometrics, and protein folding. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 200 publications
1
49
0
Order By: Relevance
“…17−19 The typical protein DUVRR spectrum is dominated by amide bands, which characterize the polypeptide backbone conformation, and aromatic amino acid bands, which report on their local environment. 19 The DUVRR spectra of both pH 2.0 and pH 6.0 HET-s (218−289) prion fibrils show sharp, intense Amide I and II bands as well as a high intensity of the C α −H band that are indicative of an extended β-sheet conformation ( Figure 3). It was found that the positions and relative intensities of all bands remained the same, which shows that the secondary cross-β core structure of HET-s (218−289) prion fibrils does not change upon reversal of the filament supramolecular chirality.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…17−19 The typical protein DUVRR spectrum is dominated by amide bands, which characterize the polypeptide backbone conformation, and aromatic amino acid bands, which report on their local environment. 19 The DUVRR spectra of both pH 2.0 and pH 6.0 HET-s (218−289) prion fibrils show sharp, intense Amide I and II bands as well as a high intensity of the C α −H band that are indicative of an extended β-sheet conformation ( Figure 3). It was found that the positions and relative intensities of all bands remained the same, which shows that the secondary cross-β core structure of HET-s (218−289) prion fibrils does not change upon reversal of the filament supramolecular chirality.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Further analysis of the Amide 1 band is required in order to obtain the types and amounts of secondary structure present; this is achieved through Fourier deconvolution and second derivative, curve fitting and spectral subtraction, for example. Multivariate analysis and other statistical methods are also increasingly being applied to the analysis of protein spectra because of their usefulness in interpreting the wealth and complexity of information contained within the spectra [21,22,23].…”
Section: Ftir Spectra Of Proteins -The Amide Bandsmentioning
confidence: 99%
“…19,20 Coupling of hydrogen-deuterium exchange (H/D exchange) with deep UV Raman (DUVRR) spectroscopy allows one to elucidate fibril core structural organization and determine the psi (Ψ) dihedral angle of the protein backbone. 18,[21][22][23] In addition, DUVRR provides valuable information about the local environment near aromatic amino acids, such as phenylalanine and tyrosine. This can be utilized to monitor the changes in protein secondary structure that occur upon protein aggregation.…”
Section: Introductionmentioning
confidence: 99%